Diagnostic Value of Electrocardiography Compared with Echocardiography in Measuring Left Ventricular Mass Index in Major Thalassemia Patients Over 10 Years of Age - Noormohammad Noori (Journal of Tehran University Heart Center, 2015)
Background: Patients suffering from major beta thalassemia need frequent blood transfusions and, if not treated well, would be at risk of heart dysfunction. This study was performed to determine the diagnostic value of electrocardiography versus echocardiography in measuring the left ventricular mass index in these patients.